Karakteristik Kompetensi Professional Guru Dalam Perspektif Imam Al-Ghazali Pada Kitab Ihya’ Ulumuddin - Muhammad, Siti Nur Holisa; Ahmad Khumaidi; M. Inzah (IAIN Ambon, 2025)
Problems in the world of education often occur today. One of them is violence committed by teachers as a reasonable punishment. Based on these problems, this study aims to determine the characteristics of professional teacher competence according to Imam Al-Ghazali in the book Ihya ‘Ulumuddin. This study uses a qualitative approach with a type of library research based on the translation of the book Ihya’ Ulumiddin and various types of references such as books, journals, and articles that are relevant to the research being conducted. The results of this study show the characteristics of professional teacher competence according to Imam Al-Ghazali in the book Ihya ‘Ulumiddin including: First, giving affection to his students. Second, emulating the Prophet. Third, not leaving advice to his students. Fourth, teaching in a gentle way. Fifth, not demeaning other knowledge. Sixth, conveying understanding according to the level of understanding of his students. Seventh, conveying material clearly. Eighth, practicing his knowledge. In addition, there are several factors that influence the professional competence of teachers, including academic qualifications, teaching experience, training and motivation.